Literature Review on the Application of Chinese Children’s Piano Works in Piano Education at Universities in Guangxi - Lu, Hao; Rattanachaiwong , Nataporn; Liu , Lingling (Journal of Roi Kaensarn Academi, 2024)
This paper explores the current status and development trends of Chinese children’s piano works in teaching within the context of piano education at universities in Guangxi. The study analyzes domestic and international literature, focusing on the application of these works in piano education, including areas such as curriculum development, teaching methods, and student learning outcomes. Using literature analysis as the primary research method, this study classifies and examines existing research and academic papers. The results indicate that while Chinese children’s piano works have been integrated into piano education in Guangxi, challenges remain in areas such as curriculum design, localization of content, and teaching methods. This study emphasizes that incorporating these works into teaching helps enhance students’ cultural identity and artistic expression, and is of significant importance for improving piano education in Guangxi universities.